A novel graded approach for improving the efficiency of Lead-Free perovskite solar cells. (15th September 2022) - Bhattarai, Sagar; Pandey, Rahul; Madan, Jaya; Muchahary, Deboraj; Gogoi, Dipankar
Highlights: A comprehensive study of lead-free PSCs are accomplished using SCAPS-1D simulating software. The novel approach of grading of the active layer is also studied. The CTM combination of Titanium oxide (TiO2 ) and 2, 2′, 7, 7′-Tetrakis[ N, N - di (4- methoxyphenyl ) amino ]-9, 9′-spirobifluorene. (SpiroOMeTAD) attains the best possible device outputs. The lesser defective MASnI3 layer at optimal thickness offers excellent efficiency of 22.3%. The present work can be valuable for futuristic device optimization of PSC. Abstract: Methylammonium tin iodide (MASnI3 ) is the most commonly used lead-free perovskite absorber material to resolve the issues related to toxic lead (Pb)-based MAPbI3 perovskite. However, conversion efficiency for MASnI3 -based perovskite solar cells (PSCs) are still struggling to compete with lead-based PSCs. Therefore, this study provides a roadmap to achieving 22.3 % conversion efficiency for MASnI3 -based PSCs through extensive device modeling. The work utilizes the graded active layer approach to attain higher excitons inside the active layer. The opto-electrical model's combined effort is considered an excellent light trapping mechanism by matching precise bandgaps 1.3 eV/1.3 eV for a higher generation of excitons. Detailed investigation and optimization of single, double, and triple graded perovskite absorber layer (PAL) have been done in terms of absorber layer thickness, temperature, back contact materials, and bulk defect density to achieve a conversion efficiency of 22.3 %. Results revealed that double-graded perovskite outperforms compared to single and triple-graded material and delivered excellent photovoltaic (PV) parameters such as short circuit current density ( JSC ) of 33.51 mAcm −2, open-circuit voltage ( VOC ) of 875 mV and fill factor ( FF ) of 75.93 %. This paper provides a smooth pathway for futuristic development and further optimization of the device lead-free MASnI3 -based PSCs.